1999
DOI: 10.4315/0362-028x-62.2.128
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Growth of Escherichia coli O157:H7 in Fresh Radish (Raphanus sativus L.) Sprout Production by Calcinated Calcium

Abstract: The inhibitory effect of calcinated calcium on the growth of Escherichia coli O157:H7 during fresh radish (Raphanus sativus L.) sprout production was studied. It was revealed that the addition of 0.4% (wt/vol) calcinated calcium into radish sprouting medium which was artificially contaminated with E. coli O157:H7 (3.0 to 3.2 log CFU/ml) completely inhibited the growth or inactivated the microorganism. When radish seed extract was used instead of radish sprout production, the same extent of growth inhibition or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…For example, Bari et al (1999) found that a 0.4% CaO treatment did not affect the quality parameters (taste, color, and appearance) of radish sprouts in comparison to untreated samples. Choi et al (2006) reported that the sour taste of kimchi treated with 0.5% CaO in powdered oyster-shell form was lower than that of the control; however, significant differences were not seen (p > 0.05) among the control and 0.05%, and 0.1% shell powder treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Bari et al (1999) found that a 0.4% CaO treatment did not affect the quality parameters (taste, color, and appearance) of radish sprouts in comparison to untreated samples. Choi et al (2006) reported that the sour taste of kimchi treated with 0.5% CaO in powdered oyster-shell form was lower than that of the control; however, significant differences were not seen (p > 0.05) among the control and 0.05%, and 0.1% shell powder treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Gandhi and Matthews (2003) reported that CaO was effective in the elimination of Salmonella from alfalfa seeds and sprouts. Bari et al (1999) reported that calcinated calcium was useful in controlling E. coli O157H7 contamination during the production of fresh radish sprouts. Sawai et al (2001b) also reported that CaO treatment effectively reduced the aerobic bacterial count in shredded cabbage.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment, however, has a minimal sanitizing effect and results in less than a 2 log 10 CFU/g reduction of bacteria on produce 2,7,19,56 . Although other sanitizers including chlorine dioxide (ClO 2 ), hydrogen peroxide (H 2 O 2 ), organic acid, and calcinated calcium solution have been evaluated 4,17,23,35 , these sanitizers have a minimal sanitizing effect which is equal to that of chlorinated water. Moreover, most of these sanitizers are made from the dilution of condensed solutions, which in handling involves some risk and is troublesome.…”
Section: Introductionmentioning
confidence: 99%
“…Ohisa et al (1999) reported that heated oyster shell powder treatment at 60 − 70℃ controlled the growth of coliform groups on wild Warabi plant. Bari et al (1999Bari et al ( , 2002 stated that heated oyster shell treatment completely inhibited the growth of microorganisms in fresh radish sprouts and on the surface of tomatoes. Choi et al (2006) reported that addition of heated shell powder preserved the quality of kimuchi.…”
Section: Introductionmentioning
confidence: 99%